People and Institutions in the Roman Empire : Essays in Memory of Garrett G. Fagan - Gatzke, Andrea F. (Mnemosyne, Supplements Ser, 2020)
Intro -- ‎Contents -- ‎Preface -- ‎In Memoriam-Garry Fagan -- ‎Figures -- ‎Abbreviations -- ‎Notes on Contributors -- ‎Part 1. Introduction -- ‎Chapter 1. Peopling the Institutions of the Roman Empire (Gatzke) -- ‎Chapter 2. Of Meter Rules, Romans, and Jesuits (Fagan) -- ‎Chapter 3. The Scholarship of Garrett G. Fagan (Lendon) -- ‎Part 2. People, Institutions, and History -- ‎Chapter 4. Caesar and the Bellum Gallicum (Potter) -- ‎Chapter 5. Commanders' Responses to Mutinies in the Roman Army (Brice) -- ‎Chapter 6. Der Einschluss der Kinder in kaiserliche Bürgerrechtskonstitutionen nach der „Reform" des Antoninus Pius im Jahr 140: Einblicke in die römische Administration (Eck) -- ‎Chapter 7. The Trial of Jesus Revisited (Riess) -- ‎Chapter 8. Quintus Arrius, the Roman Triumph, and Christianity (Pfeilschifter) -- ‎Part 3. People in Roman Society -- ‎Chapter 9. Taking the Plunge: A Twenty-First-Century Look at Roman Bathing Culture (Rogers) -- ‎Chapter 10. The Linguistic Lure of the Arena in Apuleius' Golden Ass (Edmondson) -- ‎Chapter 11. Philippianus: A Late Roman Sicilian Landowner and His Use of the Monogram (Wilson) -- ‎Cumulative Bibliography of Works by Garrett G. Fagan -- ‎Index.